My guy : redux [video recording]. (Manila : Ramon Magsaysay Center.)
Here is the first part of a film series about the late Ramon del Fierro Magsaysay, the third President of the Republic of the Philippines -- dearly loved by his people and much admired around the world. Known simply as "The Guy", Magsaysay's ideals of honesty, integrity, hard work and selfless service are legendary. His greatness of spirit aspires Asia's premier prize - the Ramon Magsaysay Award. My Guy Redux seeks to re-introduce Ramon Magsaysay to generations who have not been privileged to know him or live under his dynamic leadership. Part one of the series captures the essence of his life from childhood to manhood, focusing on the transformation of a seemingly ordinary life into a heroic life of leadership and honor. By knowing the Guy, Ramon Magsaysay, may we discover as well the everyday hero in each of us.
Keywords: Philippines -- Presidents -- Biography